Materials for printed boards and other interconnecting structures. Sectional specification set for prepreg materials, unclad (for the manufacture of multilayer boards). High performance non-halogenated epoxide woven E-glass prepreg of defined flammability (vertical burning test) for lead-free assembly Part 4-19, (28th February 2014) - British Standards Institution,
No abstract available